Pengaruh Penambahan Essential Oil Tumbuhan Cananga odorata sebagai Bahan Anestesi pada Transportasi Sistem Tertutup Benih Ikan Bileh (Rasbora sp.) - Fitria Rahmayanti; Agusriati Muliyana; M. Barru Airil Fizra Hasibuan; Mahendra; Munandar; Irhami S (Jurnal Serambi Engineering, 2024)
The bileh fish (Rasbora sp.) is one of the freshwater fish of economic value in West Aceh and Nagan Raya districts. Domestication efforts are being intensively carried out in a controlled environment so that bileh fish can be cultivated. Bileh fish require proper handling during seed transport as they are susceptible to stress and death during transport. One attempt to solve this problem is the addition of local plant essential oils in packaging media. This study aims to determine the effect of Cananga odorata plant essential oil added as an anaesthetic in the transport of bileh fish seeds on induction time, recovery and survival rate. The treatment in this research was the use of Cananga odorata flower essential oil at concentrations of 0.5 ppm (A), 1 ppm (B), 1.5 ppm (C) and 2 ppm (D). The test fish were observed and the time of induction, recovery and survival were calculated. The results showed that the essential oil of Cananga ordorata plant can be used as an anaesthetic agent in the transport of bileh fish seeds with the best concentration, namely 1 ppm (treatment B) with a survival rate after transport were 90.67% and after cultivation after transport were 81.33%. Fish reached induction time in less than 10 minutes except in treatment A (0.5 ppm) and fish recovery time in less than 8 minutes.